Comparison of ketamine-propofol mixture (ketofol) and midazolam-meperidine in endoscopic retrograde cholangiopancretography (ERCP) for oldest old patients - Ebru TK; Resul K (Dove Medical Press, 2019)
Tarıkçı Kılıç Ebru,1 Kahraman Resul21Department of Anesthesiology, Ümraniye Training and Research Hospital, İstanbul, Turkey; 2Department of Gastroenterology, Ümraniye Training and Research Hospital, İstanbul, TurkeyBackground and aim: Endoscopic retrograde cholangiopancreatography (ERCP) requires moderate-to-deep conscious sedation. Combinations of ketamine and propofol (ketofol) and of midazolam and meperidine were analyzed using the bispectral index (BIS). There is no research on the use of ketofol on very elderly patients. The aim of this study is to use BIS and offer insight into the use and safety of ketofol sedation for oldest old patients undergoing ERCP.Materials and methods: For the ERCP procedure, 168 patients aged 85+ years were enrolled in a 2-year retrospective single center study. Seventy-five patients received midazolam-meperidine (MM) sedation in 2016, while 75 patients received ketofol (KP) sedation in 2018.The two groups were compared for patient data, procedure duration, Ramsay Sedation Score (RSS), heart rate (HR), blood pressure (BP), and pulse oximetry (SpO2), BIS, facial pain score (FPS), time to achieve BIS, recovery time, and complications. The total amount of rescue medication was recorded.Results: The two groups did not differ by patient data or procedure duration (p>0.05). Group KP had significantly higher systolic and diastolic BP, HR, and SpO2 values and lower BIS scores than Group MM (p=0.0001). The two groups did not differ by time to achieve BIS scores (p>0.05). Group KP had significantly fewer complications and a shorter recovery time than Group MM (p<0.001).Conclusion: Ketofol induced sedation results in more stable vital signs and fewer complications than the midazolam-meperidine sedation regimen during ERCP in oldest old patients, indicating that ketofol can be an alternative to midazolam-meperidine.Keywords: ketofol, midazolam-meperidine, moderate to deep sedation, endoscopic retrograde cholangiopancreatography (ERCP), bispectral index (BIS), oldest old